The outcome of emergency and elective surgery in caesarean section (The Planet, 2022)
Objective: In this study our main goal is to the outcome of emergency and elective surgery in Caesarean section. Method: This prospective study was carried out at Department of Obstetrics and Gynaecology, Comilla Medical College Hospital, Comilla. Where total of 100 consecutive cases were selected for this study who underwent caesarean section. Results: During the study, 80% women underwent emergency caesarian section and 20% underwent elective caesarian section. 83 cases were spinal anesthesia, significantly higher number of women belong to emergency cases (79.5%). In 2 cases of epidural anesthesia, both underwent elective caesarian section procedure. Out of 15 cases of general anesthesia, 14(93.3%) women underwent emergency and only 1(6.7%) elective procedure. out of 80 emergency Caesarian section, 63(78.8%) babies survived and in elective caesarian section 19(95%) babies survived. Conclusion: From our study we can conclude that, maternal and fetal complications were significantly higher in the emergency caesarean section as   compared to elective caesarean section group.
Keywords: emergency; elective surgery; caesarean section